STUDI PENGEMBANGAN EKONOMI LOKAL KOTA BOGOR BERBASIS PRODUK UNGGULAN DAERAH DENGAN ANALISIS SWOT - Kuswadi Rustam; Rachmat Subarkah (Jurnal Solusi, 2021)
The processing industry contributed 19% of GRDP in 2010 - 2017 the second largest after the trade and retail sector, this reflects the city of Bogor as a tourism area and residential area because it forms the largest GRDP of the four sectors. Thus, local economic development planning focuses on the processing industry. the processing industry, which is indeed mostly processed products typical of the city of Bogor, with commodities obtained from the FGD results, including typical culinary delights, processed food, fashion, footwear, and handicrafts. Local Economic Development is expected not only to solve economic problems, but also other aspects of development, namely improving the quality of development and improvement in local communities. Therefore, through a study of local economic development in Bagor City based on Regional Leading Products with the PUD assessment method based on twelve indicators and SWOT analysis with the aim of finding superior local economic products and determining the strategy for developing the Local Economy. This research approach is using a questionnaire, collecting primary and secondary data, through interviews, qualitative (but still measurable), document studies, and Focus Group Discussions (FGD). The city of Bogor has great local economic potential that is able to have a big impact on the regional economy. Some commodities in the city of Bogor, such as the rubber processing industry into footwear products that are able to open job vacancies for the surrounding community with an average workforce of 3-7 workers. There are five commodities that have the potential to be used as a foundation for the development of the local economy, namely commodities, culinary specialties, metal craft fashion, batik crafts, and footwear. through several development strategies of each commodity as a result of this study